Fatores associados a qualidade de vida de homens com câncer de próstata - ARAÚJO, Mayra Sharlenne Moraes (2017)
Prostate cancer is the most prevalent type among men. Knowledge of the factors that alter the quality of life is fundamental for its identification and understanding, and then development of intervention strategies to prevent the decline of quality of life. The objective of this study was to evaluate factors associated with the quality of life of men with prostate cancer. This is an analytical, transversal research with a quantitative approach. The sample consisted of 226 men with prostate cancer being treated at the Aldenora Bello Cancer Hospital. To collect data, a questionnaire was used with socioeconomic, demographic, lifestyle and clinical questions and a specific questionnaire to evaluate the quality of life in cancer. EORTC- C30). As a result, 44.2% were 71-80 years old, 82.3% were self-employed, 62.8% were not retired, 90.3% had a monthly income of up to two minimum wages, 63.7% had less than eight years of study, 80.5% were married, 61.9% were from the interior of the state, 76.1% did not practice physical activity, 53.1% sought health care only when they presented a problem, 51, 3% underwent prostate withdrawal surgery. In relation to quality of life, the symptoms that most negatively influenced the quality of life were: fatigue, pain and insomnia, financial difficulty. The emotional function was the one with the lowest score on the functional scale. The variables that showed an association with quality of life were: profession, income, marital status, caregiver, financial aid, origin, smoking, physical activity, time of treatment and time of living with the disease. Advances in the area of health allow men to live with prostate cancer without loss of quality of life despite the vital crisis that cancer can cause. Knowing the factors that influence this quality of life, allows men to reflect on it and health professionals find subsidies to try to improve it.